Evaluation of the efficacy and predictive indicators of PD- 1 inhibitors combined with chemotherapy in advanced pancreatic cancer - Tiantian Zhang; Yangyang Zhou; Yue Wu; Mengting Shi; Weijie Sun; Rui Wang (Scientific Reports)
Abstract Patients with advanced pancreatic ductal adenocarcinoma (PDAC) generally face a poor prognosis and limited therapeutic options. This study aims to evaluate the clinical efficacy of combining PD- 1 inhibitors with chemotherapy as a first-line treatment for advanced PDAC, and to explore the correlation between various clinical parameters and treatment outcomes.This retrospective study analyzed the clinical data of 57 patients with advanced PDAC treated at the First Affiliated Hospital of Bengbu Medical University from January 2022 and June 2024. Patients were allocate into the two groups: the chemotherapy-alone group (29 cases) (CT), which received either the AG regimen or the mFOLFIRINOX regimen, and the imimmunotherapy plus chemotherapy group (28 cases) (ICT), which received the AG regimen or mFOLFIRINOX regimen in combination with PD- 1 inhibitors.The study compared progression-free survival (PFS), overall survival (OS), objective response rate (ORR), disease control rate (DCR), and adverse reactions between the two groups. Additionally, it analyzed the correlation between various clinical indicators and their dynamic changes over time in relation to treatment outcomes. Kaplan-Meier curves were plotted for survival analysis, and log-rank tests assessed PFS and OS differences.Univariate and multivariate Cox regression analyses identified independent risk factors for prognosis, while logistic regression assessed the correlation between these factors and treatment response.The median PFS and OS in immunotherapy plus chemotherapy group were significantly superior to those in the chemotherapy-alone group (PFS: 7.3 vs. 5.8 months, P = 0.005; OS: 12 vs. 10.2 months, P = 0.031). The ORR in the group receive immunotherapy combined with chemotherapy was also significantly higher compared to the group treated with chemotherapy alone (42.86% vs. 17.24%, P = 0.03). No significant differences were observed in the incidence or severity of treatment-related adverse events (TRAEs) and immunotherapy-related adverse events (irAEs) between the CT and ICTgroups (any grade: 93.10% vs. 96.45%, P = 0.574; grade 3 or 4: 31.3% vs. 28.57%, P = 0.839). Patients without liver metastasis, without diabetes, or those who experience a increase in SOD levels following treatment may constitute an advantageous population for immune combination therapy. In conclusion, chemotherapy combined with PD- 1 inhibitors demonstrated favorable safety and tolerability, and significantly improved PFS, OS, and ORR compared to chemotherapy alone.